Effects of DEM Sources on Hydrological Modeling: Case Study of Upstream Area in Bang Pakong River Basin,Thailand - Pyay, Pyay Thar; Polsomboon, Pongsit; Ram-Indra, Teerawat; Ruangrassamee, Piyatida (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 30, 2025)
Digital Elevation Models (DEMs) are essential tools in hydrological and geomorphological studies, providing topographic data for watershed analysis, streamflow simulation, and flood modeling. This study evaluates the performance of two global DEMs— Hydrological data and maps based on SHuttle Elevation Derivatives at multiple Scales (HydroSHEDS) and Multi-Error-Removed Improved-Terrain Hydro (MERIT Hydro) with spatial resolution of 500m by utilizing the Rainfall-Runoff-Inundation (RRI) model to simulate daily discharge in the upstream area of Bang Pakong River basin, Thailand The differences in elevation and flow accumulation were investigated. Model calibration was performed using data from 2021, and validation was conducted with data from 2019, assessing the accuracy of each DEM source in capturing streamflow dynamics. Statistical metrics, including the Nash-Sutcliffe Efficiency (NSE), coefficient of determination (R²), and Root Mean Square Error (RMSE), are employed to evaluate model performance. Results indicate that both DEMs effectively capture the overall hydrograph pattern, but their effectiveness varies across different stations. The prominent difference in the elevation especially in mountainous areas. The difference in flow accumulation demonstrates different river channel position derived from each DEM. The findings provide insights into the selection of appropriate DEMs for hydrological modeling in the region, contributing to improved water resources management and flood prediction capabilities.